Internationalization strategies of Polish fast growing enterprises - Śliwiński, Rafał (Economics and Business Review, 2012)
This paper presents internationalization strategies of Polish enterprises gathered in a qualitative empirical study. It describes internationalization motives, entry and competing strategies of Polish fast growing firms on international markets. The presented research results are important for three reasons. Firstly, as the paper represents one of the first qualitative studies of internationalization strategies of Polish fast growing enterprises. Secondly, it provides an update of the knowledge about current internationalization strategies of Polish firms which (as research results show) changed over time. Thirdly, the results of this research show directly the field where the state aid would be required in the internationalizing process of Polish companies, which may be useful for the government when considering a relevant policy. (original abstract)